The Analysis of Instructional Process through Scientific Approach on Science Subject Matter and Its Effects toward Learning Achievement - Pratiwi, Ni Luh Putu Yanti (Universitas Pendidikan Ganesha, 2017)
This study aim to describe the implementation of a scientific approach in the learning process and know the differences learning outcomes of science in terms of the levels scientific learning process in grade V at SD Negeri 1 Semarapura Tengah. This study was descriptive and inferential, the study population was a learning process in grade V SD Negeri 1 Semarapura Tengah. Samples were taken by eksidental sampling because researchers use science learning process ongoing research in class V SD Negeri 1 Semarapura Tengah is Theme 9